2013
DOI: 10.12816/0003313
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Students at Sultan Qaboos University towards the Nursing Profession = إتجاهات طلبة جامعة السلطان قابوس نحو مهنة التمريض

Abstract: abstract:Objectives: The aim of this study was to explore the attitudes of Sultan Qaboos University (SQU) students towards the nursing profession. Methods: A sample of 377 students (male = 130; female = 247) were selected from different colleges of SQU, including the College of Nursing. A questionnaire was constructed and validated to assess the attitudes of SQU students towards the nursing profession. Results: Findings revealed that both male and female students in all academic years and colleges had positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Surprisingly, a Chinese study demonstrated that parents would not encourage their children to enroll in nursing education [30]. The observed positive perception of Omani university students about the nursing profession might reflect a reporting bias, since the numbers of the nursing students outweigh those from other disciplines [31]. Secondly, other factors concerning the heath care policies to recruit nationals and media marketing of the nursing profession in Oman should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a Chinese study demonstrated that parents would not encourage their children to enroll in nursing education [30]. The observed positive perception of Omani university students about the nursing profession might reflect a reporting bias, since the numbers of the nursing students outweigh those from other disciplines [31]. Secondly, other factors concerning the heath care policies to recruit nationals and media marketing of the nursing profession in Oman should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a Chinese study demonstrated that parents would not encourage their children to enroll in nursing education [30]. The observed positive perception of Omani university students about the nursing profession might re ect a reporting bias, since the numbers of the nursing students outweigh those from other disciplines [31]. Secondly, other factors concerning the heath care policies to recruit nationals and media marketing of the nursing profession in Oman should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…And the author conducted an awareness program regarding the positive value of nursing in view to attract more students towards nursing. (6) another study conducted in China suggests that the clinical experience has no impact on the attitude but the curriculum design plays important role in shaping the attitude of nursing students towards nursing. (7) The study conducted in hong kong among high school children suggests that the students who are socially acquainted with the nurse show more likely to choose nursing as a career rather than the other students (8).…”
Section: Need Of the Studymentioning
confidence: 99%